2012
DOI: 10.1136/bmj.e3675
|View full text |Cite
|
Sign up to set email alerts
|

Dabigatran, rivaroxaban, or apixaban versus enoxaparin for thromboprophylaxis after total hip or knee replacement: systematic review, meta-analysis, and indirect treatment comparisons

Abstract: Objective To analyse clinical outcomes with new oral anticoagulants for prophylaxis against venous thromboembolism after total hip or knee replacement.Design Systematic review, meta-analysis, and indirect treatment comparisons. Medline and CENTRAL (up to April 2011), clinical trials registers, conference proceedings, and websites of regulatory agencies. Data sourcesStudy selection Randomised controlled trials of rivaroxaban, dabigatran, or apixaban compared with enoxaparin for prophylaxis against venous thromb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
154
3
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(187 citation statements)
references
References 46 publications
12
154
3
13
Order By: Relevance
“…The availability of different regimens of comparators complicates an integrated assessment of the overall efficacy and safety of new agents relative to the current standard of care, as well as indirect comparisons among the new agents, but this factor has not always been considered in published meta‐analyses for single1, 2, 3, 4, 5, 6, 7 or multiple8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18 agents. Dose regimen of the comparator has been acknowledged as a potential source of heterogeneity for a number of previous analyses 1, 2, 3, 5, 6, 10, 11, 12, 13, 14, 18.…”
mentioning
confidence: 99%
“…The availability of different regimens of comparators complicates an integrated assessment of the overall efficacy and safety of new agents relative to the current standard of care, as well as indirect comparisons among the new agents, but this factor has not always been considered in published meta‐analyses for single1, 2, 3, 4, 5, 6, 7 or multiple8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18 agents. Dose regimen of the comparator has been acknowledged as a potential source of heterogeneity for a number of previous analyses 1, 2, 3, 5, 6, 10, 11, 12, 13, 14, 18.…”
mentioning
confidence: 99%
“…A recent systematic review and meta-analysis concluded that the risk of symptomatic VTE was lower with rivaroxaban [relative risk (RR) 0.48; 95 % CI 0.31-0.75] and similar with dabigatran, when compared with enoxaparin. However, the RR of clinically relevant bleeding was higher with rivaroxaban (RR 1.25; 95 % CI 1.05-1.49) and similar with dabigatran (RR 1.12; 95 % CI 0.94-1.35) [9]. These figures suggest that chemical agents with a greater efficacy in VTE prophylaxis come at the cost of a higher risk of bleeding [9][10][11].…”
Section: Discussionmentioning
confidence: 64%
“…However, the RR of clinically relevant bleeding was higher with rivaroxaban (RR 1.25; 95 % CI 1.05-1.49) and similar with dabigatran (RR 1.12; 95 % CI 0.94-1.35) [9]. These figures suggest that chemical agents with a greater efficacy in VTE prophylaxis come at the cost of a higher risk of bleeding [9][10][11]. Rivaroxaban may also be more cost-effective than enoxaparin, with a 30-day course of 10 mg rivaroxaban costing £63.00, compared with £121.20 for a 30-day course of 40 mg enoxaparin [12].…”
Section: Discussionmentioning
confidence: 95%
“…Even though elderly patients are considered at higher risk for bleeding and venous thromboembolism (5,7,10) most studies that assess safety and efficacy of VTE prophylaxis after major orthopedic surgery did not include an independent analysis or special considerations for this population (6,13,14,(22)(23)(24)(25)(26). Therefore, recommendations of dose adjustments are only based on the assumption of a physiological impairment of renal and hepatic function that occurs with age, but not on objective evidence of the increased risk of bleeding in this group of patients (15,(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Despite that numerous studies have assessed the efficacy and safety of different anticoagulant agents in general population (12)(13)(14), there is still a lack of evidence regarding its use in special populations such as elderly patients, considering that patients who are candidates to major orthopedic surgery are frequently older than 65 years (10,15,16).…”
Section: Introductionmentioning
confidence: 99%